Fractionation of chicken egg proteome by isoelectric point in liquid phase - Gulyás, Gabriella; Jávor, András; Radócz, Tünde; Simon, Ádám; Czeglédi, Levente (Acta Agraria Debreceniensis, 2014)
The application of proteomics is relevant to physiology, reproduction, immunology, muscle and lactational biology in animal science, altough its use is still limited. One of the greatest challenges of proteome analysis is the reproducible fractionation of the complex protein mixtures. The fractionation methods can increase the probability of biomarker protein discovery. The fractionation by liquid-phase isoelectric focusing is one of the prefractionation methods. As a result, protein fractions can be easily collected, pooled and refractionated. There is a lack in the knowledge of gel-based proteomic methods of egg as only a limited number of protocols can be found in the literature, thus sample purification and fractionation require a time consuming optimisation procedure. The aim of this study was to fractionate egg yolk and white proteins by isoelectric point in liquid phase.